(untitled) (Nigerian Journal of Pharmaceutical Research, 2022)
Background: Benign prostate hyperplasia (BPH) is an age-related disease characterized by enlargement of the prostate gland and its associated complications. Objectives: Phytochemicals responsible for hypolipidemic and antioxidants effects of leaf extract of Laportea aestuans in androgen-induced BPH Wistar rats were evaluated. Methods: Thirty (30) male Wistar rats were divided into five groups of 6 rats each. BPH was induced by subcutaneous injection of dihydrotestosterone (DHT) and estradiol-valerate (10:1) daily for 28 days. The diseased control and drug control groups were given subcutaneous olive oil and oral finasteride (5 mg/kg.bw) respectively after induction of BPH. Rats in the test groups were given 50 and 100 mg/kg.bw of the extract orally for 28 days respectively, following disease induction. The lethal dose LD50 and antioxidants activity of plant extracts, lipid profile and prostate specific antigen (PSA) level of the rats were assayed using standard biochemical tests. Results: Secondary metabolites detected were alkaloids (20.11±0.07 mg/kg), tannins (1.32±0.21), and saponins (11.41±0.14). PSA level was significantly decreased (P<0.05) when compared with the diseased control. The lipid profile assay revealed a significant (P<0.05) reduction in Triacylglycerol (62%), Cholesterol (27%) and low density lipoprotein (LDL) (19%) but high density lipoprotein cholesterol (HDL-C) concentration increased by 41%. The extracts also improved SOD (26%), catalase (38%) and reduced glutathione (36%) levels but reduced malondialdehyde (MDA) level by 28%. Conclusion: These findings therefore provide a scientific evidence for the traditional use of L. aestuans in the management of complications associated with BPH which could be a function of the various phytochemicals detected in the plant